2006
DOI: 10.1590/s1516-14392006000100010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of CdTe sources used for deposition of CdTe thin films by close spaced sublimation technique

Abstract: Unlike other thin film deposition techniques, close spaced sublimation (CSS) requires a short source-substrate distance. The kind of source used in this technique strongly affects the control of the deposition parameters, especially the deposition rate. When depositing CdTe thin films by CSS, the most common CdTe sources are: single-crystal or polycrystalline wafers, powders, pellets or pieces, a thick CdTe film deposited onto glass or molybdenum substrate (CdTe source-plate) and a sintered CdTe powder. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…This source-plate was prepared by sublimating a CdS/propyleneglycol paste. Details about the equipment can be seen elsewhere [9]. The pressure of the system was varied between 5 and 15 Torr, using argon or a mixture of oxygen/argon.…”
Section: Experimetal Methodsmentioning
confidence: 99%
“…This source-plate was prepared by sublimating a CdS/propyleneglycol paste. Details about the equipment can be seen elsewhere [9]. The pressure of the system was varied between 5 and 15 Torr, using argon or a mixture of oxygen/argon.…”
Section: Experimetal Methodsmentioning
confidence: 99%
“…CSS-CdTe grains size is about 290nm, PVD-CdTe giains size is 13nm (Moutinho et al, 2008). Unlike other thin film deposition techniques, the distance between the source and the substrate is very short with millimeters or less, the source chosen is very important, because the source strongly affects the control of the deposition parameters, especially the deposition rate (Pinheiro et al, 2006). The close space sublimation (CSS) technique is characterized by the short distance between the source and the substrate, which is usually less than 1 mm.…”
Section: Close Space Sublimation (Css)mentioning
confidence: 99%
“…So far only few systematic studies have addressed the influence of particle size on deposition rate in CSS CdTe deposition. Only Pinheiro et al [15] showed considerable deviations between CdTe powders, pastes and plates. The influence of the particle size on the deposition rate is studied in our work.…”
Section: Introductionmentioning
confidence: 99%